EVALUATION OF NEUROLOGICAL MANIFESTATIONS IN HUMAN IMMUNODEFICIENCY VIRUS-AIDS PATIENTS ADMITTED TO SOUTH INDIAN TERTIARY CARE HOSPITAL – A CROSS-SECTIONAL STUDY - TEJAVATH, ARUN SINGH; MATHUR, AMIT; SINGH, PRATIMA; SUMAN, SUPRIYA; RAJ, PREETI; VENKATESHWARA T, MURALI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to describe, evaluate, and analyze neurological manifestation in human immunodeficiency virus HIV positive patients admitted to a tertiary care center. Methods: The study was a prospective cross-sectional study, in which 103 HIV patients were analyzed. All patients were interviewed face to face and evaluated by the investigator with particular reference to neurological manifestations. They were classified into various stages of HIV using the World Health Organization staging system. Results: The mean age in males was 37 (standard deviation [SD] 8.0) years and in females 35 (SD 7.0) years. A greater proportion of females were diagnosed in the asymptomatic state during screening, either during pregnancy or when the spouse was found to be positive. Headache was the most common neurologic symptom and fundus abnormalities were the most common neurological sign documented in patients. The mean CD4 counts in males are 156.5/mm3 and in females are 229.57/mm3 whereas the mean absolute leukocyte count in males is 1088.30/mm3 and in females is 1473.52/mm3. The CD4 counts showed a better correlation with the occurrence of neurological manifestations than absolute leukocyte count. Conclusion: Headache was a significant predictor of the occurrence of neurological complications (p=0.01). CD4 counts were significantly lower in patients with neurological complications and most of the neurological manifestations; on the contrary, all the opportunistic infections were documented in patients with CD4 counts below 200/mm3. Neurological complications did not show any correlation with the patient being on anti-retroviral therapy.